Potential of Groundwater Reserves in Jeneponto Regency of South Sulawesi Province - Hatta, Mukhsan Putra; Badaruddin, Sugiarto; Faisal, Zulvyah; Puspita, Devi Ayu (INTEK: Jurnal Penelitian, 2020)
The community, both individuals and groups, need water for daily and other needs. From the various types of needs, the water for drinking water is a top priority, above all other necessities.Excessive exploitation of groundwater that exceeds the ability of aquifers to provide groundwater due to competition for various interests can cause a continuous decline in groundwater level and will certainly reduce the potential for groundwater availability in the aquifer. In this research, the potential of groundwater in Jeneponto’s aquifers in several locations is examined using in situ pumping test. From the pumping test results, it is known that the potential of groundwater reserve in Jeneponto Regency is quite significant and is spread in several districts with a minimum discharge supply of 4 litres per second. However, some procedures must be taken to protect the availability of groundwater in the regency from the technical aspects for example the determination of pumping location, the depth of groundwater pumping and the maximum pumping discharge allowed, and also all steps that support groundwater recharge.